COMPASS and Implementation Science: Improving Educational Outcomes of Children with ASD - Ruble, Lisa A (Springer, 2015)
This Brief examines COMPASS – the Collaborative Model for Promoting Competence and Success – a consultation-based intervention specialized for children with Autism Spectrum Disorder (ASD). Based on the Evidence-Based Practices in Psychology (EBPP) framework, the volume describes the processes that strengthen the expert support relationships between consultant and teacher (i.e., implementation) and between teacher and student (i.e., intervention). In addition, the Brief addresses how consultation methods work within COMPASS, with teachers learning from consultants' implementation methods to tailor instructions that are specific to students' educational and personal factors. This unique framework corresponds with current, widespread research and aims to provide more effective educational services for students with ASD during their crucial formative years.